IJTIHAD DAN PERANANNYA DALAM PENGHARMONIAN PENGAMALAN UNDANG-UNDANG SYARIAH DI DUNIA ISLAM MASA KINI - Hassan, Abdullah @ Alwi (Jurnal Syariah, 2019)
Since the nineteenth century, most Muslim countries had endeavoured to reestablish and reorganize the practice of Shari 'ah Law. In order to reinstitutionalize the practice of this law, they have to reopen the "Gate ofijtihiid (the use of individual reasoning)" which is believed to be closed in the Third Century of the Hijrah(or in the Ninth Century of the Christian Era). In order to revive the practice of ijtihiid, they have adopted various legal mechanisms to solve numerous problems and adapt the law to the new and difforent conditions and situations. Those mechanisms are altakhayyur (the eclectic expedient) and al-talfiq (combining the doctrines of more than one school) which have become two eclectic devices. In addition, other mechanisms such as the doctrine ofSiyiisah Shari 'iyyah (the policy of administrative justice within the limits assigned to it by the Syariah), ma~lalJah (public interest) and others have been used. One of new approaches in applying those mechanisms, is the introduction of various statutory legislations which has been promulgated by the national legislature, either by parliament or state legilative assembly. The state purpose of this stalutory legislation is to implement the Law efficiently and as well as to harmonise administratively between the national legal system, that was introduced by the former colonial power and the Shari 'ah Law. For Muslim countries this method of legislation is considered permissible as long as it does not contradict with the principle of Islamic jurisprudence even though as ifit has moved towards the introduction of Islamic statutory law rather than they just adhere to the jurists' law, as it occurred in the early development of the Shari 'ah Law. However, this tends to become more nationalistic in nature, which is against the universality of Shari 'ah Law. Therefore such element of nationalistic inclination should be removed in order to upgrade it to a global legal system, apart from safeguarding the national aspects of each locality that implements the law.